PENGARUH GAYA HIDUP, DOMPET DIGITAL DAN LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN PADA MAHASISWA FEB-UNIMA - Lembong, Herningsih Sutri; Kaligis, Jenny Nancy; Allo, Patriella Taruk (Bisnis-Net, 2025)
This research aims to analyze the influence of lifestyle, digital wallets and financial literacy on the financial behavior of students at the Faculty of Economics and Business, Manado State University (FEB-UNIMA). The background of this study is based on the phenomenon of student financial behavior that tends to be consumptive, has difficulty saving, and does not understand the importance of long-term financial planning. This study uses a quantitative approach with a survey method by distributing questionnaires to active students majoring in Management and Accounting, class of 2021–2024 who use digital wallets and are recipients of KIP-Kuliah scholarships. The data analysis technique used is Partial Least Square (PLS) with the help of SmartPLS 4 software. The results of the study show that lifestyle, digital wallet, and financial literacy simultaneously have a significant effect on student financial behavior. Partially, the three variables also have a significant effect. Thus, this study emphasizes the importance of improving financial literacy as well as managing lifestyle and using digital wallets wisely to create healthy financial behavior in students.